(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2025)
ABSTRACT One of the streams that has influenced Islamic philosophy is the Mu’tazilah, which emphasizes reason over all other considerations through the application of theology or kalam science. According to its etymology, it means "people who separate themselves," and the development of Ancient Greek philosophy signifies the start of critical and logical thinking, with philosophers making important contributions across a range of disciplines. Similarities exist in the rational reason that forms the foundation of thought. Using the literature study research method to present a conversation in the form of the Mu’tazilah’s logic and reasoning toward Greek thought and to determine the logic of the Mu’tazilah stream of reasoning toward Greek thought.The study’s findings demonstrate that. Aristotle’s ideas are significantly impacted by mu’tazilah philosophy in a number of ways. As a powerful school of Islamic theology, Mu’tazilah attempts to integrate theological and philosophical ideas, especially those of Aristotle. There are multiple primary findings: Reasonable and logical reasoning Mu’tazilah interprets and comprehends Islamic teachings using logical and rational approaches that are influenced by Greek philosophy, particularly Aristotle. They employ reasoning to demonstrate the existence of Allah’s promises and threats (Al-Wa’du wal Wa’id), the justice of Allah (Al-Adl), and the unity of Allah (Tawhid). Keywords: Mu’tazilah school, Ancient Greek thought, Logic, Reasoning